Psychological empowerment and engagement in income generating activities among rural women in Yobe State, Nigeria - Musa, Zara Mallam; Ahmad, Aminah; Omar, Siti Zobidah; Musa, Abubakar (International Organization of Scientific Research, 2017)
Poverty is a universal phenomenon that affects both developed and the developing nations. This has become predominant obstacle in Africa particularly among women in rural communities in Nigeria. It is therefore necessary to adopt a measure through engagement in income generating activities so as to fight against poverty for a better livelihood. The current study attempts to determine the relationship between psychological empowerment and engagement in income generating activities among rural women in Yobe state, Nigeria. Selfadministered questionnaire was used to collect data from 262 participants who were purposively selected. The result from structural equation modeling indicates significant contribution (42%) of psychological empowerment to engagement. Findings from this study show that all the four dimensions of psychological empowerment namely; meaningfulness, self-determination, competence and impact significantly contributes to rural women engagement. However there is need to consider the personality aspect of these rural women so as to boost their morale towards engagement.